Respuesta :

Answer:

(x + 1)² (5x + 4)

Step-by-step explanation:

f(x) = 5x³ + 14x² + 13x + 4  ---------->> factor the polynomial completely

use the rational root theorem:

= (x + 1) 5x³ + 14x² + 13x + 4

                     x + 1

           

= 5x² + 9x² + 13x + 4

                x + 1

= 5x² + 9x² + 4x + 4

                       x + 1

= 5x² + 9x + 4

break expression into groups

= (5x² + 4x) + (5x + 4)

factor out 5x²+4

= x(5x + 4) (x + 1)

factor out common terms : 5x + 4

= (5x + 4) (x + 1)

= (x+1) (5x + 4) (x + 1)

refine:

=  (x + 1)² (5x + 4)